Social Media Marketing on Buying Interest with Brand Image as Mediation in Fashion Thrift Products - Wijayanto, Ibnu; Fajri, Anisa (Economics and Business International Conference Proceeding, 2024)
This study aims to analyze and describe the Influence of Social Media Marketing on Buying Interest with Brand Image as Mediation in Fashion Thrift Products (Case Study on Students of the Faculty of Business Economics, University of Muhammadiyah Semarang Fashion Thrift Users The method in this study uses a questionnaire with a total of 96 respondents, with the sampling technique used non probability sampling. The "convenience sampling" technique is a technique for determining samples based on certain considerations, namely where sampling is done by determining special characteristics that are in accordance with the research objectives.